A pair of forward and reverse slow-mode shocks detected by Ulysses at ∼5 AU - Ho, Christian M.; Tsurutani, B.T.; Lin, N.; Lanzerotti, L.J.; Smith, E.J.; Goldstein, B.E.; Buti, B.; Lakhina, G.S.; Zhou, X.Y. (My University, 1998)
We report the first finding of a pair of forward and reverse slow-mode shocks in the distant heliosphere using plasma and magnetic field data from the Ulysses spacecraft located at 5.3 AU and 9°S heliolatitude. The slow-mode shocks are found to occur in a compressed magnetic field (low plasma ) region within a co-rotating interaction region (CIR). We find Mach numbers to be 0.3–0.5 with respect to forward/reverse slow shocks. Across each shock, the solar wind velocities jump by at least 40 km/s. The increases in plasma density and ion temperature accompany a decrease in the magnetic field. The shocks are also found to have velocities of 60 km/s and 115 km/s and thicknesses between 7.5-12.6×104 km (much larger than the ion inertial length, ∼10³ km). Low frequency plasma waves are detected by the Ulysses URAP instrument at the slow-mode shock transition regions. However, the waves are not of sufficient amplitude to provide enough anomalous resistivity through wave-particle interactions for shock dissipation. Low energy (∼30–90 keV) electron enhancements directed along the local magnetic field are also found associated with the slow shocks, indicating the ability of the shocks to accelerate interplanetary particles. This finding imply that more slow shocks might be found in the CIR magnetic compressed regions (where plasma is squeezed out) at large heliospheric distances.
Keywords: Plasma waves; Heliospheric; Magnetic field; Ulysses; Shocks